2020
DOI: 10.3389/fneur.2020.562634
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Headache in Patients With Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-Analysis of 14,275 Patients

Abstract: Background: Coronavirus disease 2019 (COVID-19) started to spread globally since December 2019 from Wuhan, China. Headache has been observed as one of the clinical manifestations in COVID-19 patients. We aimed to conduct a comprehensive systematic review and meta-analysis to estimate the overall pooled prevalence of headache in COVID-19 patients.Methods: PubMed, Scopus, ScienceDirect, and Google Scholar databases were searched to identify studies published between December 2019 and March 2020. Adult (≥18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 33 publications
2
65
2
5
Order By: Relevance
“…Some studies have reported a lower prevalence of headache compared with our study and have not found a relationship between COVID severity and presence of headache. For example, in a meta-analysis of 86 studies (n=14,275), the pooled prevalence of headache was much lower than that of our study (10.1%), with no significant difference in headache prevalence among severe/critically-ill vs. non-severe COVID-19 patents (p=0.78) 28 . Similar to the population in our study, one survey study from Turkey of patients with COVID-19 infection treated in an outpatient setting, found that new-onset headaches occurred in 33% of the population, and more common among those with COVID-19 compared to controls 29 .…”
Section: Discussioncontrasting
confidence: 81%
“…Some studies have reported a lower prevalence of headache compared with our study and have not found a relationship between COVID severity and presence of headache. For example, in a meta-analysis of 86 studies (n=14,275), the pooled prevalence of headache was much lower than that of our study (10.1%), with no significant difference in headache prevalence among severe/critically-ill vs. non-severe COVID-19 patents (p=0.78) 28 . Similar to the population in our study, one survey study from Turkey of patients with COVID-19 infection treated in an outpatient setting, found that new-onset headaches occurred in 33% of the population, and more common among those with COVID-19 compared to controls 29 .…”
Section: Discussioncontrasting
confidence: 81%
“…Some studies have reported a lower prevalence of headache compared with our study and have not found a relationship between COVID severity and presence of headache. For example, in a meta-analysis of 86 studies ( n = 14,275), the pooled prevalence of headache was much lower than that of our study (10.1%), with no significant difference in headache prevalence among severe/critically-ill vs. non-severe COVID-19 patents ( p = 0.78) [ 28 ]. Similar to the population in our study, one survey study from Turkey of patients with COVID-19 infection treated in an outpatient setting, found that new-onset headaches occurred in 33% of the population, and more common among those with COVID-19 compared to controls [ 29 ].…”
Section: Discussionmentioning
confidence: 62%
“…7 We also included 6 studies published between December 2019 and March 2020 from a previous meta-analysis. 8 We excluded review articles, opinion articles, case-reports, preprint server articles, and studies performed either on populations <18 years old or animal models (See Supplementary Methods and Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%